Exploring the influential factors on online investment platform - Gazali, Haneffa Muchlis; Adeyemi, Adewale Abideen; Syed Jaafar Alhabshi, Syed Musa (Institute of Electrical and Electronics Engineers Inc., 2017)
The objective of this study is to identify the variables that significantly determine the intention to use online investment platform. This study extended the TAM into four other variables, namely, perceived security, perceived financial return, perceived religiosity and Islamic worldview. A survey of 246 Muslims of online banking users in Kuala Lumpur and Selangor. The data were analyzed using Structural equation modeling (SEM) using AMOS 16. From the analysis, the data has revealed that five factors determine the intention to use online investment platform from the potential investor's point of view. The recommendation were also proposed.